Dukungan Sosial dan Penyesuaian Diri terhadap Motivasi Belajar pada Mahasiswa Perantauan Luar Jawa di Kabupaten Banyumas - Sungkowardani, Sefia; Hamzah, Imam Faisal; Nur'aeni, Nur'aeni; Wulandari, Dyah Astorini (Universitas Muhammadiyah Purwokerto, 2022)
Adapting to new environments plays a crucial role in enhancing students' enthusiasm for learning. This study investigates the effects of social support and self-adjustment on learning motivation among international students from outside Java who are studying in Banyumas Regency. Using a quantitative approach, the research employed scales to measure social support, self-adjustment, and learning motivation. The study sampled 150 international students in their second semester. The measurement instruments included a learning motivation scale (reliability = 0.716), a social support scale (reliability = 0.724), and a self-adjustment scale (reliability = 0.784). Multiple linear regression analysis was conducted to evaluate the impact of social support and self-adjustment on learning motivation. The findings revealed a significant effect, with an Fvalue of 3.129 and a significance level (p) of 0.047 (p < 0.05), indicating that both social support and self-adjustment have a positive influence on learning motivation. The results underscore the importance of fostering robust social support systems and facilitating effective self-adjustment strategies for international students. Institutions should consider implementing targeted support programs to enhance social integration and self-adjustment skills. This may include mentorship programs, peer support groups, and workshops focused on cultural adaptation and personal development.